Correlation Strength Assessment of Animal Husbandry Components to the Implementation of ASEAN Good Animal Husbandry Practices: A case study in layer farming - Eko Sugeng PRIBADI; Hanifa Hanun; Agung Puji Haryanto; Deddy Cahyadi Sutarman; Sinta Sri Utami; Rahmat Hidayat Harahap; Safika Safika; Alfred John Morris Kompudu; Luuk Schoonman; Gunawan Budi Utomo; Afton Attabany; Fadjar Sumping Tjatur Rasa; Ni Made Ria Isriyanthi (Jurnal Ilmu-Ilmu Peternakan, 2023)
ASEAN Good Animal Health Practice (GAHP) is a joint product of ASEAN member countries to be applied in laying farms. The Research aimed to explore management practices of laying farms in accordance with the guidelines from ASEAN GAHP. South Lampung District and East Lampung District were the chosen locations in this Research.  The ASEAN GAHP-based questionnaires were arranged and used for this Research. A variety of data analysis were conducted namely normality analysis, validity analysis, reliability analysis, descriptive analysis, and correlation analysis technique. The Result showed there were no significant difference were found between South Lampung District and East Lampung District farmers in the implementation of GAHP components in layer farms. Application of Veterinary Control Number (Nomor Kontrol Veteriner, NKV) issued by Government becomes a strong driver for farmers to implement the ASEAN GAHP. The Research concluded the components which have a strong relationship in the implementation of ASEAN-GAHP were waste management, personnel hygiene, transportation, water quality and treatment, and surveillance and diseases control.